Determinants of Macroeconomic Variables on the Net Asset Value Performance of Sharia Mutual Funds for the 2019–2024 Period - Suryadi Alamsyah; Peni Sawitri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The performance of Islamic mutual funds in Indonesia has fluctuated in recent years. Net Asset Value (NAV) reached its highest level in 2020, but declined sharply in 2021 and 2022. From 2023 to the present, NAV has not fully recovered despite showing an upward trend. Based on these conditions, this study aims to analyze the effect of inflation, exchange rate, interest rate (BI Rate), and GDP on the NAV of sharia mutual funds for the period 2019–2024. A quantitative method using the Vector Error Correction Model (VECM) approach was used to assess the short-term and long-term relationships. Monthly secondary data were processed through stationarity, cointegration, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD) tests. The results show that inflation has a significant negative effect in the short and long term. The exchange rate has a significant positive effect, while interest rates are insignificant, indicating that Islamic investors are less interested in interest rates. GDP has a significant positive effect in the short term but not in the long term, meaning that economic growth only has a temporary impact on NAV.